Hollow silica particles and compositions comprising the same

CN122916154APending Publication Date: 2026-10-16ONAI FUKUTOKU CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610421712.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-09
Filing Date
2026-04-01
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]但其缺点在于,引进中空结构需要复杂的制备工艺,制备工艺上的任何细微变化都会导致颗粒尺寸、壁厚和孔结构的易变,因此,在均匀保持并精密控制中空二氧化硅颗粒的物理化学特性方面存在局限性

Benefits of technology

[0030] According to one aspect of the present invention, hollow silica exhibits significantly superior uniformity and silica wall material properties, making it highly usable in applications involving high-functionality precision chemicals and biomaterials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916154A_ABST
    Figure CN122916154A_ABST
Patent Text Reader

Abstract

The present invention relates to a hollow silica particle characterized by having a type IV adsorption-desorption characteristic in nitrogen isothermal adsorption-desorption, and having a closure point at a relative pressure of 0.75 to 0.85, and having an excellent particle dispersion index. The hollow silica particle of the present invention has a remarkably excellent particle uniformity, and thus, can have an excellent usability in various application fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to hollow silica particles and compositions comprising them. Background Technology

[0002] Hollow silica particles are widely used in various industrial fields due to their unique hollow structure, chemical stability, high specific surface area, and low density. They are used as a core material in applications such as drug delivery systems, adsorbents, sensors, optical materials, thin films, thermal insulation agents, and cosmetics.

[0003] The hollow structure offers flexibility in adapting the physical and chemical properties for various applications, providing novel functionalities not available with existing silica particles. Specifically, hollow silica particles, due to their hollow structure, have low density, thus providing a high specific surface area. Furthermore, the particle size, wall thickness, and pore size can be precisely adjusted according to synthesis conditions, resulting in broad applicability across a wide range of applications. In addition, the surface of silica particles can be replaced with various chemical functional groups, thereby adjusting hydrophilicity and hydrophobicity, and imparting biocompatibility. For example, in pharmaceutical or cosmetic applications, the internal space of hollow silica particles can serve as a storage space for drugs or physiologically active substances, while the outer surface of the silica particles can be functionalized by incorporating suitable functional groups or ligands.

[0004] However, its disadvantage is that the introduction of hollow structure requires a complex preparation process. Any slight change in the preparation process will lead to changes in particle size, wall thickness and pore structure. Therefore, it has limitations in uniformly maintaining and precisely controlling the physicochemical properties of hollow silica particles.

[0005] Due to the versatility and hollow structure of silica particles, their applications are gradually expanding, particularly in the integration of environmentally friendly precision chemical materials and biomaterials. Therefore, in traditional applications utilizing the physicochemical properties of hollow structures, there is a demand to develop high-quality hollow silica that can meet the diverse requirements of high-functionality precision chemical or biomaterial applications.

[0006] Prior technology documents

[0007] Patent documents

[0008] (Patent Document 1) Japanese Registered Patent JP7218651B2 Summary of the Invention

[0009] The problem to be solved

[0010] In one aspect, the present invention provides hollow silica, which has excellent physicochemical properties in various application fields.

[0011] In one aspect, the present invention provides a hollow silica, which has a low refractive index, a low dielectric constant and excellent wear resistance, and when applied to a coating film, it can form a coating film with uniform low refractive and low reflective optical properties.

[0012] Solution to the problem

[0013] Hollow silica particles according to one embodiment of the present invention are characterized by having type IV adsorption-desorption characteristics during nitrogen isothermal adsorption-desorption and having a closure point at a relative pressure of 0.75 to 0.85, and having a particle dispersion index of 1.7 or higher as expressed by Formula 1 below.

[0014] [Formula 1]

[0015] D V / FWHM V

[0016] In Equation 1 above, D V The volume-average particle size (FWHM) is derived from dynamic light scattering analysis. V This represents the maximum half-width at half-maximum (HWHM) of hollow silica particles in the volumetric particle size distribution diagram.

[0017] According to one embodiment of the hollow silica particles, the hollow dispersion index of the hollow silica particles, as expressed by Formula 2 below, can be 1.5 or higher.

[0018] [Equation 2]

[0019] D h / FWHM h

[0020] (In Equation 2 above, D) h FWHM represents the average diameter of the hollow cavity obtained from transmission electron microscopy images. h (This represents the maximum half-height width in the hollow dimension distribution diagram)

[0021] According to one embodiment of hollow silica particles, the volume average particle size (D) of the hollow silica particles is... V ) and number-average particle size (D n The ratio of (D) V / D n This can satisfy 1 to 1.3.

[0022] According to one embodiment of the hollow silica particles, the BET specific surface area of ​​the hollow silica particles can be 50 to 100 m². 2 / g, pore volume can be 0.4 to 0.6 cm³. 3 / g.

[0023] According to one embodiment of the hollow silica particles, the average pore size of the hollow silica particles, calculated using the BJH method based on nitrogen desorption, can be 20 to 30 nm.

[0024] According to one embodiment of hollow silica particles, the hollow silica particles, in the differential value diagram of logarithmic pore size and pore volume versus logarithmic pore size using BJH, can have a single peak in the range of pore size from 2 to 50 nm.

[0025] According to one embodiment of hollow silica particles, the volume average particle size (D) of the hollow silica particles is... V The diameter of the hollow core can be 60 to 90 nm, and the average diameter of the hollow core (D) can be 60 to 90 nm. h It can be 50 to 80 nm.

[0026] According to one embodiment of the hollow silica particles, the absolute value of the Zeta potential of the hollow silica particles can be 40mV or more.

[0027] A dispersion according to one embodiment of the present invention comprises the above-described hollow silica particles.

[0028] An optical thin film according to one embodiment of the present invention comprises the aforementioned hollow silicon dioxide particles.

[0029] The effects of the invention

[0030] According to one aspect of the present invention, hollow silica exhibits significantly superior uniformity and silica wall material properties, making it highly usable in applications involving high-functionality precision chemicals and biomaterials.

[0031] According to one aspect of the present invention, hollow silica has low refractive index, low dielectric constant and excellent wear resistance, and the particles have excellent uniformity of physical properties. The coating film containing hollow silica can have uniform low reflectivity and low refractive index optical properties. Attached Figure Description

[0032] Figure 1 and Figure 2 This is a transmission electron microscope (TEM) image of hollow silica according to one embodiment.

[0033] Figure 3 This is a schematic diagram of the nitrogen adsorption-desorption isotherm of hollow silica according to one embodiment.

[0034] Figure 4 This is a pore distribution diagram of hollow silica according to one embodiment. Detailed Implementation

[0035] Unless otherwise defined, the technical and scientific terms used in this specification have the meanings commonly understood by those skilled in the art to which this invention pertains. Known functions and configurations that may obscure the essence of this invention in the following description and drawings are not described in detail.

[0036] The embodiments described in this specification can be modified in various other ways, and the technology according to one implementation example is not limited to the embodiments described below. Furthermore, the embodiments of one implementation example are intended to describe the invention more completely to those skilled in the art.

[0037] Furthermore, the singular form used in the specification and the attached patent claims may be understood to include the plural form unless otherwise indicated in the context.

[0038] In addition, unless otherwise specified, all units used in this specification are by weight. For example, the unit of % or ratio means weight % or weight ratio. Unless otherwise defined, weight % refers to the weight of a certain component in the whole composition.

[0039] Furthermore, the numerical ranges used in this specification include upper and lower limits, and all values ​​within those limits. They also include all increments logically derived within the defined form and width of the range, all double-limited values, and all possible combinations of the upper and lower limits of numerical ranges defined in different forms. Unless otherwise specified in this specification, values ​​exceeding the numerical range due to experimental errors or rounding are also included within the defined numerical ranges.

[0040] The term "comprising" in this specification is an open-ended expression that has the same meaning as expressions such as "possessing," "containing," "having," or "characterized by," and does not exclude elements, materials, or processes not otherwise listed. Furthermore, the term "substantially comprising" means including the constituent elements recited in the claims as essential constituent elements, but may also include non-essential constituent elements that do not substantially affect the effect.

[0041] Unless otherwise defined in this specification, the average aperture size (diameter) can be measured by a dynamic light scattering analyzer. The average aperture size (diameter) refers to the average aperture size (diameter) based on volume.

[0042] The present invention will now be described in detail through various embodiments or examples. It should be noted that this description is not limited to the various embodiments or examples described herein, and other embodiments or examples may be combined. Therefore, the claims referenced within the scope of the patent claims are merely examples of embodiments and should not be construed as simply a combination of the technical concept of the present invention and the referenced claims; combinations thereof with various claims should also fall within the scope of the technical concept of the present invention.

[0043] According to one aspect of the present invention, hollow silica particles are characterized by having type IV adsorption-desorption characteristics during nitrogen isothermal adsorption-desorption and having a closing point at a relative pressure (P / P0) of 0.75 to 0.85, and having a particle dispersion index of 1.7 or higher as expressed by Formula 1 below.

[0044] [Formula 1]

[0045] D V / FWHM V

[0046] In Equation 1 above, D V The volume-average particle size (FWHM) is derived from dynamic light scattering analysis. V This represents the full width at half maximum (FWHM) of hollow silica particles in the volumetric particle size distribution diagram.

[0047] The aforementioned hollow silica particles, by incorporating a hollow structure, possess low density and high specific surface area, thus exhibiting excellent usability as a common heat insulation agent and optical material. Furthermore, due to their Type IV nitrogen adsorption-desorption characteristics as defined by IUPAC and the aforementioned particle dispersion index, they demonstrate excellent properties in solute adsorption, storage, and release, making them highly usable as carriers or storage media such as drug delivery systems, catalyst supports, and adsorbents.

[0048] Specifically, the hollow silica particles exhibit a closing point at a relative pressure (P / P0) of 0.78 to 0.85, specifically 0.80 to 0.85. This closing point is a physical property indicating the mesoporous characteristics of the hollow silica particles, and it is related to the pore size distribution, mesopore connectivity, and mesopore surface characteristics. Therefore, the closing point can characterize pore properties that cannot be expressed by combinations of pore volume, pore size, and pore specific surface area.

[0049] Specifically, the particle dispersion index represented by Formula 1 above can be 1.75 or higher, 1.8 or higher, or 1.85 or higher; and non-limitingly, it can be 10 or lower, 9 or lower, or 5 or lower. Specifically, the particle dispersion index represented by Formula 1 above can be 1.7 to 10, 1.75 to 9, 1.8 to 5, or 1.85 to 5.

[0050] The BET specific surface area of ​​the aforementioned hollow silica particles can be 40 to 120 m². 2 / g, 50 to 100m 2 / g, 60 to 90m 2 / g, specifically, can be 65 to 85m 2 / g.

[0051] The pore volume of the aforementioned hollow silica particles can be from 0.3 to 0.7 cm³. 3 / g, 0.35 to 0.65cm 3 / g, 0.4 to 0.6cm 3 / g, specifically, can be 0.45 to 0.55cm 3 / g.

[0052] The average pore size of the aforementioned hollow silica particles, calculated using the BJH method based on nitrogen desorption, can be 15 to 35 nm, 18 to 32 nm, specifically 20 to 30 nm. The aforementioned BET specific surface area, pore volume, and average pore size can be measured using BET analysis based on nitrogen adsorption-desorption. These hollow silica particles contain mesopores and the aforementioned pore structure, thereby effectively adsorbing or storing solutes without compromising the thermal insulation or optical properties provided by the hollow structure. For example (but not limited to), by incorporating a catalyst into the hollow silica particles, reactants can rapidly contact the catalyst particles through low diffusion resistance, and products generated by the catalytic reaction can be rapidly discharged to the outside. Therefore, excellent catalyst activity can be maintained even at high space velocities.

[0053] According to one embodiment, in the logarithmic scale plot of pore size and pore volume of the aforementioned hollow silica particles calculated using the Barrett-Joyner-Halenda (BJH) method, a single peak can be observed in the pore size range of 2 to 50 nm. Specifically, in the nitrogen adsorption-desorption experiment of the aforementioned hollow silica particles, with the logarithmic scale pore size (w) calculated using the BJH method as the x-axis and the differential value of the logarithmic scale pore size of the pore volume (dV / dlog(w)) as the y-axis, the hollow silica particles exhibit a single peak in the mesopore diameter range, i.e., in the range of 2 to 50 nm. That is, the presence of a single peak in the log(w) vsdV / dlog(w) plot indicates that highly uniform mesopores are formed on the silica walls.

[0054] According to one embodiment, the hollow silica particles described above can have a particle size of 50 to 100 μm. 2 BET specific surface area per g and 0.4 to 0.6 cm² 3 / g pore volume.

[0055] According to one embodiment, the hollow dispersion index of the hollow silica particles, as expressed by Formula 2 below, can be 1.5 or higher.

[0056] [Equation 2]

[0057] D h / FWHM h

[0058] In equation 2 above, D h FWHM represents the average diameter of the hollow cavity obtained from transmission electron microscopy images. h This represents the maximum half-width at half-height in the hollow dimension distribution diagram. Specifically, the average diameter (D) of the hollow structure mentioned above... h ) and FWHM h This represents the average hollow diameter obtained from TEM image analysis of any 100 particles and the FWHM obtained from the diameter distribution map.

[0059] Specifically, the hollow dispersion index represented by Equation 2 above can be 1.6 or higher, 1.7 or higher, 1.8 or higher, 1.9 or higher, 2.0 or higher, 2.1 or higher, or 2.2 or higher; and non-limitingly, it can be 10 or lower, 9 or lower, 8 or lower, or 5 or lower. Specifically, the hollow dispersion index represented by Equation 2 above can be 1.5 to 10, 1.6 to 9, 1.8 to 8, 2.0 to 5, or 2.2 to 5.

[0060] The particle dispersion index and the hollow dispersion index are respectively satisfied to be 1.7 or above and 1.5 or above, preferably 1.8 or above and 2.0 or above. Therefore, each particle of hollow silica can have a uniform hollowness. Preferably, it can have excellent usability in the field of optical materials where it is necessary to maintain the uniform refractive index of small areas over a large area.

[0061] The hollow portion of the hollow silica particles is 45% to 75%, 48% to 70%, or more specifically, 50% to 65%.

[0062] The volume average diameter (D) of the above-mentioned hollow silica particles V The diameter can be 50 to 150 nm, 55 to 130 nm, 58 to 120 nm, 60 to 100 nm, or 60 to 90 nm. Furthermore, the average diameter of the hollow core (D...) hThe wavelength range can be 40 to 100 nm, 45 to 95 nm, 50 to 90 nm, 55 to 90 nm, 60 to 85 nm, or 65 to 85 nm.

[0063] According to one embodiment, the volume average diameter (D) V The diameter can be 60 to 90 nm, and the average diameter of the hollow core (D) h The diameter can be 50 to 80 nm, specifically, the volume average diameter (D) V The diameter can be 65 to 90 nm, and the average diameter of the hollow core (D) h The diameter can be 50 to 80 nm, or the volume average diameter (D) V The diameter can be 70 to 85 nm, and the average diameter of the hollow core (D) h The wavelength can be 55 to 75 nm.

[0064] According to one embodiment, the volume-average particle size (D) of the above-mentioned hollow silica particles is... V ) and number-average particle size (D n The ratio of (D) V / D n The number-average particle size (D) of the above-mentioned hollow silica particles can meet the requirements of 1 to 1.3. n The value (D) represents the average aperture size (diameter) calculated through dynamic light scattering analysis. V / D n The particle size distribution index (D) is an indicator of the particle size dispersibility of hollow silica particles. It is known that ordinary hollow silica particles not only exhibit polydispersity, but also show non-uniformity in the aforementioned hollow dispersion index. Specifically, the aforementioned ratio (D...) V / D n () can be 1 to 1.25 or 1 to 1.2.

[0065] According to one embodiment, the absolute value of the Zeta potential of the hollow silica particles described above can be 40 mV or more. Specifically, the hollow silica particles described above can have a negative Zeta potential, and the absolute value can be 45 mV or more or 50 mV or more. Non-limitingly, the absolute value can be 70 mV or less.

[0066] In one aspect, the present invention provides a dispersion comprising the aforementioned hollow silica particles. The dispersion may be a dispersion dispersed in a polar solvent, for example, it may be an aqueous dispersion, an alcohol dispersion, or a dispersion dispersed in an organic solvent. The aqueous dispersion may further contain a solvent miscible with water.

[0067] The aforementioned miscible solvents can be alcohols, acetic acids, carboxylic acids, ketones, amines, amides, or ethers. Specifically, examples include acetic acid, methanol, ethanol, isopropanol, ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, butanediol, glycerol, diethoxyamine, vinyl acetate, dimethylformamide, formic acid, N-methylpyrrolidone, propylene glycol monomethyl ether acetate, etc., but are not limited to these.

[0068] In another aspect, the present invention provides an article comprising the aforementioned hollow silica particles. This article can be any of the following: a drug delivery system, a catalyst, an adsorbent, a sensor, an optical material, a thin film, a heat-insulating agent, and a cosmetic. The article comprising the aforementioned hollow silica particles, wherein the hollow silica particles are uniformly dispersed, provides superior performance in terms of physical properties to achieve the desired purpose.

[0069] According to one embodiment, the above-mentioned article can be an optical thin film. Optical thin films are required to have uniform and excellent optical properties (refractive index, transmittance, reflectance, etc.). Existing hollow silica particles can effectively improve optical properties, but the physicochemical properties of the particles are not uniform. The disadvantage is that the uniformity of optical properties is poor throughout the entire area of ​​the optical thin film, especially over a large area.

[0070] However, the optical film according to the present invention comprises the hollow silica particles described above, thus exhibiting uniform and excellent optical properties throughout the entire film area. The hollow silica particles of the aforementioned optical film possess uniform physical properties and are uniformly dispersed, resulting in uniformity of optical properties such as refractive index over a large area. Therefore, in the field of optical films requiring uniformity, superior optical effects can be provided. Furthermore, the uniform dispersion of the hollow silica particles suppresses stress concentration within the film, thereby improving durability against external forces and increasing scratch and impact resistance. Moreover, the uniform hollow distribution of the aforementioned optical film provides superior thermal insulation performance, photothermal safety, and other mechanical and chemical properties compared to existing optical films.

[0071] Specifically, the optical thin film is not particularly limited if it can adjust the characteristics of light such as reflection, transmission, refraction, and dispersion. For example (but not limited to), the optical thin film can be an anti-reflection or low-reflection film, a low-refractive-index film, a polarizing film, a prism film, a diffusion film, a brightness enhancement film, or a transmission adjustment film.

[0072] The following describes specific examples and experimental cases. However, the examples and experimental cases described below are only partial examples, and the technology described in this specification is not limited thereto.

[0073] <Example 1>

[0074] 1) Preparation of the first solution

[0075] In a glass reactor equipped with a stirrer, 4,273 g of pure water was added, along with 71 g of sodium aluminate (Na2O 41 wt%, Al2O3 49 wt%) and 4 g of sodium hydroxide. After mixing, the mixture was heated to 60 °C and maintained thereafter to prepare the first solution.

[0076] 2) Preparation of the second solution

[0077] In another container, at room temperature (25±5℃), 17,165 g of pure water and 487 g of sodium silicate solution (Na2O 9.5 wt%, SiO2 29 wt%) were mixed and stirred to prepare the second solution.

[0078] 3) Preparation of aqueous hollow silica sol

[0079] In a first solution kept under heat, 5,652 g of a second solution was slowly added over 4 hours to prepare an aqueous sol containing core particles. Then, the aqueous sol containing core particles was heated to 70°C and maintained thereafter, and 12,000 g of the second solution was slowly added over 4 hours to form a shell around the core particles, thus preparing an aqueous silica sol. 910 g of hydrochloric acid (SAMCHUN Chemical, 36%) was added to the aqueous silica sol, and after stirring for 1 hour, it was allowed to mature for 24 hours to prepare a hollow silica aqueous sol with internal pores.

[0080] 4) Preparation of hollow silica dispersion

[0081] Then, the concentration was achieved to 4,200 g using an ultrafiltration membrane with a molecular weight cutoff of 300,000 Daltons. The mixture was then repeatedly diluted and concentrated with pure water to remove impurities, yielding a concentrated hollow aqueous sol with a conductivity of 68 μS / cm. Diisopropylamine was added to the concentrated hollow aqueous sol, and the pH was adjusted to 11. The sol was then placed in a high-pressure reactor and subjected to hydrothermal synthesis at 160°C for 6 hours, forming a dense shell with increased density. This was followed by repeated concentration and dilution using an ultrafiltration membrane with a molecular weight cutoff of 300,000 Daltons to remove impurities, thus preparing a hollow silica dispersion containing hollow silica particles.

[0082] <Example 2>

[0083] In the preparation step 1) of the first solution in Example 1 above, 5,402 g of pure water, 90 g of sodium aluminate and 5 g of sodium hydroxide were mixed. In the preparation step 2) of the second solution above, 16,036 g of pure water and 455 g of sodium silicate solution were added. Otherwise, the hollow silica dispersion was prepared using the same method as in Example 1.

[0084] <Example 3>

[0085] In the preparation step 1) of the first solution in the above embodiment, 3,604 g of pure water, 60 g of sodium aluminate and 3 g of sodium hydroxide were mixed. In the preparation step 2) of the second solution, 17,834 g of pure water and 506 g of sodium silicate solution were added. Otherwise, the hollow silica dispersion was prepared using the same method as in Example 1.

[0086] <Example 4>

[0087] In the above-described embodiment, in step 1) of preparing the first solution and step 3) of preparing the hollow silica aqueous sol, the temperature of the first solution is heated to 70°C and maintained, and in step 3) of preparing the hollow silica aqueous sol, the core particle aqueous sol is heated to 80°C and maintained. Otherwise, the hollow silica dispersion is prepared using the same method as in Example 1.

[0088] <Comparative Example 1>

[0089] In the preparation step 3) of the hollow silica aqueous sol in Example 1 above, the mixture formed by adding the second solution to the first solution which is heated to 98°C and held at one time is heated to 98°C and held at one time to complete the preparation of the silica aqueous sol. Otherwise, the hollow silica dispersion is prepared using the same method as in Example 1.

[0090] <Comparative Example 2>

[0091] In the above-mentioned step 3) of the preparation of hollow silica aqueous sol in Example 1, the mixture formed by adding the second solution into the first solution which is heated to 70°C and held at one time is heated to 70°C and held at that temperature to complete the preparation of silica aqueous sol. Otherwise, the hollow silica dispersion is prepared using the same method as in Example 1.

[0092] <Evaluation of Hollow Silica Particles>

[0093] (Experimental Example 1) Measurement of Hollow Dimensions

[0094] like Figures 1 to 2 As shown, after acquiring transmission electron microscopy images of hollow silica particles, the hollow diameter of any 100 hollow silica particles was measured, and the average hollow diameter and the FWHM in the hollow size distribution map were also measured. h The results are recorded in Table 1 below.

[0095] (Experimental Example 2) Dynamic Light Scattering (DLS)

[0096] Dynamic light scattering analysis was performed using a light scattering spectrometer (Litesizer DLS700, Anton Paar) with a 658 nm semiconductor laser equipped with a laser Doppler system. The concentration of hollow silica particles in the dispersion was adjusted to 0.1% by weight after the solvent was replaced with alcohol from water, and the analytical sample was used. Scattered light was detected using a detector (avalanche photodiode, APD) located at 90° to the incident light source, and the particle distribution was calculated using the CONTIN routine. Table 1 below shows the calculated volume-average particle size (D) of the hollow silica particles. V Number-average particle size (D) n ), FWHM v And Zeta potential value.

[0097] (Experimental Example 3) Pore Characteristic Analysis

[0098] To understand the specific surface area and pore structure of hollow silica particles, nitrogen adsorption experiments were conducted using a 3Flex (Mircromeritics) analyzer. Before nitrogen adsorption analysis, the samples were pretreated for 8 hours under vacuum at 150°C. Nitrogen adsorption and desorption were then performed, and the BET (Brunaer-Emmett-Teller) specific surface area, pore volume, and average pore size (diameter) were calculated. The results are recorded in Table 1. Figure 3 The figure shown is the BET isotherm for nitrogen adsorption-desorption. Figure 4 The diagram shows the porosity.

[0099] [Table 1]

[0100]

[0101] As shown in Table 1 above, it was confirmed that the hollow silica particles in the hollow silica dispersion of the embodiment exhibited Type IV behavior during nitrogen isothermal adsorption-desorption, with closure points at a minimum relative pressure of 0.78 and a maximum of 0.83. Furthermore, it was also confirmed that D... h / FWHM h It must be 2 or higher, specifically 2.5 or higher. For example, such as... Figure 3 As shown, the hollow silica of Example 1 has a closure point under a relative pressure of 0.83. The above results indicate that the hollow silica of Example 1 has very uniform mesopores, but the pore entrances are narrower than the internal pores, indicating that material diffusion is not easy. Therefore, when the hollow silica of the examples is combined with polymers that form a continuous phase to form an article, the hollow structure in the article can be well preserved, and the significant effects of the hollow structure can be fully utilized.

[0102] Furthermore, the pore characteristic analysis conducted in the above-mentioned case confirmed that the hollow silica particles in the embodiment had an average pore size of 25.7 nm to 33.2 nm and an average pore volume of 0.47 to 0.54 cm³. 3 / g, the average pore size (diameter) of the comparative example hollow silica particles ranged from 29.4 nm to 31.2 nm, and the average pore volume ranged from 0.62 to 0.89 cm³. 3 / g.

[0103] Furthermore, during the aforementioned pore characteristic analysis, in the differential values ​​of pore size and pore volume on a logarithmic scale relative to pore size for the hollow silica particles in the examples using BJH, only a single peak was observed in the pore size range of 25 to 40 nm. For example, as... Figure 4 As shown, the hollow silica of Example 1 exhibits a single peak at approximately 31 nm. In contrast, the hollow silica of Comparative Examples 1 and 2 simultaneously show single peaks in the pore size range of 10 nm to 20 nm and in the pore size range of 20 to 35 nm.

[0104] The above results demonstrate that the hollow silica particles in the embodiments possess uniform colloidal characteristics, hollow characteristics, and porous characteristics.

[0105] <Coating Film Evaluation>

[0106] Low-reflection coating liquids containing the hollow silica dispersions prepared in the above examples and comparative examples were prepared, and the physical properties of the coating films prepared from the coating liquids were evaluated.

[0107] Specifically, 60 grams of a siloxane resin diluted in propylene glycol methyl ether at a solid content concentration of 50% by weight, 90 grams of concentrated hollow silica aqueous sol dispersed in propylene glycol methyl ether at a concentration of 0.3% by weight, and 850 grams of propylene glycol methyl ether were added and mixed to prepare a low-reflection coating liquid with a concentration of 3% by weight. After preparing the coating film using the method described in the experimental example below, the physical properties were evaluated.

[0108] First, the low-reflection coating liquid was applied to a microscope slide (LK LAB KOREA, microscope slide) using a spin coating method. The slide was then heat-cured at 120°C for 30 minutes to obtain a sample with a low-reflection coating film that is 20 cm long, 20 cm wide, and 100 nm thick.

[0109] Reflectance, haze, transmittance, and refractive index were measured at 10 random locations on the prepared sample, and the mean and standard deviation were calculated. Reflectance was measured using a Konica Minolta CM 3600A spectrophotometer, while haze and transmittance were measured using an HM-150 HAZE METER manufactured by Murakami Color Technology Laboratory. Furthermore, refractive index was measured using an ellipsometer after a 1-micron-thick coating was formed on the silicon wafer; the evaluation results are recorded in Table 2 below.

[0110] [Table 2]

[0111]

[0112] As shown in Table 2 above, the hollow silica coating film of the embodiments exhibits good results in terms of reflectivity, haze, transmittance, and refractive index. In particular, it can be confirmed that the total area has uniform optical properties. In contrast, the total area of ​​Comparison 1 and Comparison 2 exhibits non-uniform optical properties.

Claims

1. A hollow silica particle, characterized in that, It exhibits type IV adsorption-desorption characteristics during nitrogen isothermal adsorption-desorption and has a closure point at a relative pressure of 0.75 to 0.

85. Its particle dispersion index, expressed by Equation 1, is greater than 1.

7. [Formula 1] D V / FWHM V In Equation 1 above, D V The volume-average particle size (FWHM) is derived from dynamic light scattering analysis. V This represents the maximum half-width at half-maximum (HWHM) of hollow silica particles in the volumetric particle size distribution diagram.

2. The hollow silica particles according to claim 1, characterized in that, The hollow silica particles have a hollow dispersion index of 1.5 or higher, as expressed by Formula 2 below. [Equation 2] D h / FWHM h In equation 2 above, D h FWHM represents the average diameter of the hollow cavity obtained from transmission electron microscopy images. h This represents the maximum half-height width in the hollow dimension distribution diagram.

3. The hollow silica particles according to claim 1, characterized in that, The volume-average particle size D of the hollow silica particles V With number-average particle size D n The ratio of D V / D n Satisfy conditions 1 to 1.

3.

4. The hollow silica particles according to claim 1, characterized in that, The hollow silica particles have a BET specific surface area of ​​50 to 100 m². 2 / g, pore volume 0.4 to 0.6 cm³ 3 / g.

5. The hollow silica particles according to claim 1, characterized in that, The hollow silica particles have an average pore size of 20 to 30 nm, calculated using the BJH standard method for nitrogen desorption.

6. The hollow silica particles according to claim 1, characterized in that, In the differential value diagram of the logarithmic scale pore size and pore volume of the hollow silica particles using BJH, a single peak is observed in the range of pore size from 2 to 50 nm.

7. The hollow silica particles according to claim 1, characterized in that, The volume-average particle size D of the hollow silica particles V The diameter is 60 to 90 nm, and the average diameter of the hollow core is D. h The wavelength is 50 to 80 nm.

8. The hollow silica particles according to claim 1, characterized in that, The absolute value of the Zeta potential of the hollow silica particles is above 40mV.

9. A dispersion comprising hollow silica particles according to any one of claims 1 to 8.

10. An optical thin film comprising hollow silica particles according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Hollow silica particles, dispersions of hollow silica particles, and films

    JP7218651B2